Serendipitous CO‐ and RhI‐Induced Coupling of Bidentate Phosphaalkenes with Expulsion of Bis(trimethylsilyl)ketene Leading to RhIII‐Coordinated Dianionic Tetradentate Ligands. Issue 5 (8th October 2015) - Lungu, Daniela; Bîrzoi, Roxana M.; Goers, Christine; Bartsch, Rainer; du Mont, Wolf‐W.; Daniliuc, Constantin; Jones, Peter G.
Abstract: In the RhCl chelate complexes of C ‐bis(trimethylsilyl)‐ P ‐alkyl(diphenylphosphanyl)aminophosphaalkenes1 [(Me3 Si)2 C=PN(R)PPh2 ;1a : R = 1‐Ada;1b : R = t Bu], the P=C double bonds are preferentially η 2 ‐( P, C )‐coordinated to Rh I, as shown by the structure determination of trans ‐[RhCl{(Me3 Si)2 C=PN(R)PPh2 }]2 (5a ) and by the comparison of the 31 P NMR spectra of cis‐ and trans ‐[RhCl{(Me3 Si)2 C=PN(R)PPh2 }]2 (5a, b ), [RhCl(PPh3 ){(Me3 Si)2 C=PN(R)PPh2 }] (6a, b ), [RhCl(CO){(Me3 Si)2 C=PN(R)PPh2 }] (7a, b ) and [(cod)Rh(μ‐Cl)2 Rh{(Me3 Si)2 C=PN(R)PPh2 }] (8a, b ). With excess of [RhCl(cod)]2, the ligand (Me3 Si)2 C=PN(CH2 Ph)PPh2 (1c ) forms solid trinuclear complex10 containing two Rh(Cl)cod moieties attached to the central chelate unit [Rh(Cl)(1c )]: one Rh atom is attached by (terminal) P→Rh(Cl)cod coordination and the other one by bridging Rh(μ‐Cl)2 Rhcod. The reactions of the complex [RhCl(CO)(PPh3 )2 ] with ligands1a or1b unexpectedly led, with elimination of bis(trimethylsilyl)ketene, to racemic Rh III –chloro complexes [RhCl({Ph2 PN(R)P}2 C(SiMe3 )2 )] (11a, b ) containing the dianionic tetradentate chelating "bis‐PNP" ligands (Me3 Si)2 C{P (–) N(R)PPh2 }2 (12a, b ) η 4 ‐coordinated to Rh III (CN 5). The CO‐induced formation of Rh III complexes11a and11b also occurred when7a and7b were treated with another equivalent of ligand1a or1b, when [RhCl(CO)2 ]2 was mixed with more than 2 equiv. of1a or1b, and even bubbling gaseous CO into a solution containing6a provided11a and bis(trimethylsilyl)ketene. Abstract : The reaction of [RhCl(CO)(PPh3 )2 ] with bidentate phosphaalkene ligands1 [(Me3 Si)2 C=PN(R)PPh2 ;1a : R = 1‐Ada;1b : R = t Bu] leads, with elimination of bis(trimethylsilyl)ketene, to racemic Rh III –chloro complexes [RhCl({Ph2 PN(R)P}2 C(SiMe3 )2 )] (11a, b ) each containing a dianionic η 4 ‐coordinated ligand. CO is essential for the unusual ligand coupling reaction.